Evaluation of motivation in the quality management system of Peruvian Glass S.A. - Torres Zavala, Nancy Georgina (2021)
The objective of this investigation was to evaluate the motivation and deter[1]mine the motivational indexes that affect the quality management system measured in one of their primary targets: “Percentage of Reprocess type A curved caused by the person” of the Peruvian Glass S.A. company by applying questionnaire of audit of the human system motivation: ASH-MOT to 73 people of the production process during five months. The investigation concludes that the indices of conscience of results and perceived meaning most affect the labor motivation in the sample under study.